Second-Look Needle Arthroscopy after Prior Surgical Treatment for Cartilage Lesions of the Ankle: The Amsterdam and New York City Perspectives - Alex Walinga MD; James J. Butler MB BCh BAO; Jari Dahmen MD; Sjoerd Stufkens MD, PhD; Guillaume Robert BS; John G. Kennedy MD, MCh, MMSc, FFSEM, FRCS (Orth); Gino M M. M.J. Kerkhoffs MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle; Sports Introduction/Purpose: The purpose of this prospective study was to evaluate the quality of the reparative cartilage during second-look needle arthroscopy following talar osteoperiostic grafting from the iliac crest (TOPIC) and autologous osteochondral transplantation (AOT) procedures for the management of large osteochondral lesions (OCLs) of the talus. Methods: Patients who underwent second-look needle arthroscopy following either TOPIC or AOT procedure were prospectively recruited. The primary outcome was the assessment of the quality of the reparative cartilage via second-look needle arthroscopy scored by the International Cartilage Repair Society (ICRS) score. The secondary outcomes were the number and nature of ad-hoc needle arthroscopy interventions and complications associated with these interventions. Results: Five patients underwent second-look needle arthroscopy following TOPIC procedure and 11 patients underwent second-look in-office needle arthroscopy following AOT. The mean ICRS in the TOPIC cohort was 9.4 ± 1.0 at a mean time of 24.4 months following the index procedure. The mean ICRS in the AOT cohort was 10.6 ± 1.3 at a mean time of 58.8 months following the index procedure. No complications were observed in either cohort. Conclusion: This study demonstrated that AOT and TOPIC lead to high-quality reparative cartilage at short-term to mid-term follow-ups, but further studies with larger patient cohorts and longer follow-ups are warranted. Furthermore, second-look needle arthroscopy is a safe and viable minimally invasive procedure that can effectively evaluate the quality of reparative cartilage following surgical intervention for OCLs of the talus. In addition to arthroscopic evaluation of the reparative cartilage, this procedure has therapeutic capabilities and can resect bony and soft tissue sources of anterior ankle impingement.